2004
DOI: 10.1542/peds.113.2.305
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Constraint-Induced Movement Therapy for Children With Cerebral Palsy With Asymmetric Motor Impairment

Abstract: Pediatric CI therapy produced major and sustained improvement in motoric function in the young children with hemiparesis in the study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
410
0
14

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 398 publications
(447 citation statements)
references
References 22 publications
8
410
0
14
Order By: Relevance
“…The results described by Taub et al 16 showed significant improvements in the quality and amount of use of the more impaired limb, compared with previous studies 20,21 . These improvements were explained by the combination of casting with intensive training of contralateral limb using functional activities.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…The results described by Taub et al 16 showed significant improvements in the quality and amount of use of the more impaired limb, compared with previous studies 20,21 . These improvements were explained by the combination of casting with intensive training of contralateral limb using functional activities.…”
Section: Discussionmentioning
confidence: 53%
“…There was considerable variation between instruments used and between the methods used to evaluate the outcomes presented. The instruments most used were the Emerging Behaviors Scale (two studies 16,17 ), Pediatric Motor Activity Log (two studies 16,17 ) and Jebsen-Taylor Test of Hand Function (two studies 15,18 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rehabilitation of the upper limbs has been associated with fine motor tasks, exercises performed in a unilaterally way, and coordination exercises using both arms (Damiano, 2006;Diez-Alegre et al, 2012;Howcroft et al, 2012;Huber et al, 2010;Hutzler, Lamela-Rodríguez, Laiz-Mendoza, Díez, & Barak, 2013). These tasks have been proven effective in the treatment of CP and other central nervous system disorders such as hemiplegias (Dean and Shepherd, 1997;Taub, Ramey, DeLuca & Echols, 2004). On the other hand, lower limb rehabilitation generally consists on gross motor activities involving repetitive and coordinated movements with both limbs (walking, cycling, etc.…”
Section: Discussionmentioning
confidence: 99%
“…An RCT has demonstrated the effectiveness of constraint-induced therapy in children with congenital hemiplegia. 132 Other strategies including inhibitive casting, lycra splinting, treadmill training, and functional electrical stimulation remain to be studied in pediatric stroke. The UK guidelines recommend muscle strengthening to improve function and minimize contractures, Botox injections for spasticity, and ankle-foot orthoses for gait and contracture prevention.…”
Section: Disease-specific Therapiesmentioning
confidence: 99%